„Doorgaan en niet vergeten!“ Otto Schumacher (1908–1988). Communist, hulpverlener en verzetsman - Krutzen, Marcel (Stichting Historische Kring „Het Land van Herle“, 2024)
Keywords: Aachen (Region); Antifaschismus; Flüchtlingshilfe; Heerlen; Kommunismus; Konzentrationslager; Politischer Gefangener; Soziale Situation; Steinkohlenbergbau; Widerstand

Maastrichtse industriëlen en het Belgische annexisme in de jaren 1918–1919 - Beaumont, Eddy de (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2023)
Abstract: „During and immediately after the First World War the Belgian government developed plans to annex parts of the Netherlands after the war, such as the province of Limburg. How did industrialists in the capital Maastricht respond to these Belgium goals? In this article, I explore the perspectives of an industrialist, a state detective and an economist in this matter. The industrialist was a fierce opponent of annexation, while the state detective was convinced that annexionists, those who were in favour of annexation, should mainly be found among major industrialists. The economist, on the other hand, did not rule out the possibility that some of Maastricht’s traders and industrialists would prefer a connection with Belgium. How did they come to these conclusions and to what extent did their considerations and other sources provide an answer to the research question of this article? Taking both gossip and facts into account, we may conclude that indeed there could have been traders and industrialists who supported the Belgian aspirations and preferred to join Belgium. However, the general claim that, in Maastricht especially, major industrialists were in favour of annexation lacks any factual evidence.“
Keywords: Annexion; Erster Weltkrieg; Industrie; Maastricht; Provinz Limburg (Niederlande); Widerstand

De heldinnen van de Eerste Wereldoorlog - Aert, Marina van (Oudheidkundige Kring Kalmthout vzw, 2022)
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage2/2024/02/17/file_27/9509498.pdf
Keywords: Besetzung; Elektrozaun; Erster Weltkrieg; Fluchthilfe; Kalmthout; Schmuggel; Widerstand

Résistance sans frontières. Enquête sur les groupes d'espionnage et les lignes d'évasion (1940–1943) - Jongh, Paul E. de (Brepols, 2019)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage2/2020/03/16/file_4/8841746.pdf
Keywords: Besetzung; Kloster Val-Dieu; Widerstand

Grenzeloos verzet. Over spionerende monniken, ontsnappingslijnen en het Hannibalspiel, 1940–1943 - Jongh, Paul E. de (Brepols, 2018)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage2/2022/02/13/file_7/9122753.pdf
Keywords: Besetzung; Kloster Val-Dieu; Widerstand

Spannung und Widerstand an der niederländischen Grenze 1930–1940. Exil, Widerstand und niederländische Unterstützung. Zwei Beispiele in der Region Kleve-Nijmegen - Brauer, Jan (Dies- und jenseits der Grenze. Translokale Prozesse und ihre Einwirkung auf den deutsch-niederländischen Grenzraum, 2017)
Keywords: Deutscher Flüchtling; Exil; Grenzgebiet; Kleve (Kreis Kleve); Nimwegen; Widerstand

Een Kalmthouts verhaal van „passeurs“ en weggevoerden in 1915–1916 - Aert, Marina van (Calmthoutania, 2015)
Keywords: Besetzung; Elektrozaun; Erster Weltkrieg; Fluchthilfe; Kalmthout; Schmuggel; Widerstand

Grenzüberschreitender Widerstand und niederländische Unterstützer. eine Fallstudie zur Sozialistischen Arbeiterpartei (SAP) im Raum Duisburg - Graber, Adolf; Tietz, Manfred (Nationalsozialistische Herrschaft und Besatzungszeit. Historische Erfahrung und Verarbeitung aus niederländischer und deutscher Sicht, 2000)
Keywords: Duisburg; Grenzüberschreitende Kooperation; Sozialdemokratie; Sozialismus; Widerstand

Sozialer Kontext von Illegalität und Widerstand in der Grenzregion Twente - Hilbrink, Coen (Nationalsozialistische Herrschaft und Besatzungszeit. Historische Erfahrung und Verarbeitung aus niederländischer und deutscher Sicht, 2000)
Keywords: Besetzung; Twente; Widerstand

Flucht über die niederländische Grenze bei Elmpt. Aus den Erinnerungen des Heinrich Lehnsen 1939 bis 1945 - Backhausen, Manfred (Heimatbuch Kreis Viersen, 1991)
Keywords: Deutscher Flüchtling; Widerstand; Zollbeamter

Het „militaire“ verzetswerk in het district Doetinchem - Lichtendahl, M. J. (Er op of er onder. Hoe Achterhoek en Lijmers de Duitsche bezetting doorstonden en ervan werden bevrijd. Gegevens over den bezettingstijd, het verzet en de bevrijding, 1970)
Keywords: Befreiung; Besetzung; Doetinchem; Widerstand; Zweiter Weltkrieg